Assessment of The Impact Factors in The Process of Customer Loyalty in Buying Cosmetic Brands in Iran Pharmacies - Ramin Radmanesh (International Journal of Pharma and Bio Sciences, 2022)
In today's business, the issue of competition between different companies in the market is increasingly important. A company's brand has particular value and credibility, and is considered the most valuable asset for that company. Customer loyalty to a company's brand is one of the vital strategies for gaining and maintaining a position in the market. Customer loyalty to the company's brand is related to the satisfaction or behavior of the complainant. Therefore, in the present study, the influencing factors on the customer loyalty trend of cosmetic and health brands referring to pharmacies in Iran were explored. The research population was all female customers who referred to pharmacies in Iran to buy cosmetic products, and according to the number of more than 100 thousand people, 384 women were selected as an available sample using Morgan's table. Our aim is to investigate the factors affecting customers' loyalty to buying cosmetic brands in Tehran pharmacies. In order to achieve this goal, we seek to answer the question, "What are the impact factors in the loyalty process of customers in the purchase of cosmetic brands in Tehran pharmacies?" In other words, the size of the statistical population was 384 female Customers who bought cosmetics and hygiene products in pharmacies in Tehran. Spearman's non-parametric test was used to assess the correlation between the frequency of visits to the pharmacy and the parameters of loyalty, awareness, quality, price, image, and brand promotion, and the Kruskal–Wallis test was used to check the effect of the investigated variables on brand loyalty. A level below 0.05 was considered significant. Based on the results, brand awareness, quality, and price of a brand's products had a significant relationship with brand loyalty. In such a way, the product awareness, higher quality, and reasonable price led to more loyalty towards that cosmetic brand, and customers purchased more of its products.